Ethanomedicinal properties of Euphorbiaceae family- A comprehensive review - Sangha Ramesh Bijekar; MC Gayatri (International Journal of Phytomedicine, 2014)
Ethanomedicine is the study of traditional medical practice which is concerned with the cultural interpretation of health, diseases and illness and also addresses the healthcare seeking process and healing practices. Euphorbiaceae is among the large flowering plant families consisting of a wide variety of vegetative forms some of which are plants of great importance. The family Euphorbiaceae is assessed taxonomically and phylogenetically in the light of different disciplines of botany. This article provides ethanomedicinal properties of 103 members of Euphorbiaceae family, it includes botanical name, local name, plant parts used for treatment and their reported activity. This study has revealed that Euphorbiaceae members act as an effective remedy for many diseases like diaheria, jaundice, diabetes, inflammation, etc.